Note to the Spanish Pharmacopoeia, IX edition: Bismuth subcarbonate - García Villanova, Dr. R.; Thomas, J.; Bosch, F. (Ars Pharmaceutica (Internet), 1965)
A gravimetric and complexometric technics of evaluation of bismuth subcarbonate has been revised. We recommended a complexometric technic, using EDTA and a potassium iodide, Pyricotechol Violet and thiourea as indicator indifferently, in order to include it in new Spanish Pharmacopeia edition.